Perlindungan Hukum terhadap Kreditur Selaku Penerima Jaminan Fidusia Pasca Dikeluarkannya Putusan Mahkamah Konstitusi Nomor 18/PUU-XVII/2019 - Suharyadi, Suharyadi (Universitas Negeri Malang, 2022)
This study aimed to analyze the juridical implications, the urgency of the new concept of default, losses suffered by creditors, and legal protection for creditors after the Constitutional Court Decision Number 18/PUU-XVII/2019. This study used a normative juridical method with a case and legislation approach. The juridical implication of the Constitutional Court Decision Number 18/PUU-XVII/2019 was the non-fulfillment of the element of legal certainty due to differences in the concept of default in the Constitutional Court Decision Number 18/PUU-XVII/2019 with the provisions of Article 1243 of the Civil Code. The urgency of the new concept of default in the Constitutional Court Decision Number 18/PUU-XVII/2019 was to provide legal protection for debtors when a default is declared unilaterally by the creditor. Losses experienced by creditors were categorized into cost losses, losses on damaged goods, and losses on profits that should be obtained. Legal protection for creditors was carried out in a preventive and repressive manner.This study aimed to analyze the juridical implications, the urgency of the new concept of default, losses suffered by creditors, and legal protection for creditors after the Constitutional Court Decision Number 18/PUU-XVII/2019. This study used a normative juridical method with a case and legislation approach. The juridical implication of the Constitutional Court Decision Number 18/PUU-XVII/2019 was the non-fulfillment of the element of legal certainty due to differences in the concept of default in the Constitutional Court Decision Number 18/PUU-XVII/2019 with the provisions of Article 1243 of the Civil Code. The urgency of the new concept of default in the Constitutional Court Decision Number 18/PUU-XVII/2019 was to provide legal protection for debtors when a default is declared unilaterally by the creditor. Losses experienced by creditors were categorized into cost losses, losses on damaged goods, and losses on profits that should be obtained. Legal protection for creditors was carried out in a preventive and repressive manner.